Investment cost specifications revisited - Mathias Mier; Valeriya Azarova (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2022)
Policymakers misjudge results of technology-rich optimization models because those models specify investment cost differently and thus are not equally sensitive towards changing financing cost and discount rates. We apply an intertemporally optimizing power market model to analyze three different investment cost specifications. The three specifications lead to a substantially different pace and rate of adoption for specific generation technologies and diverging carbon prices. The first assumes that an investment is financed by equity only, the second one applies a mix of equity and debt, and the third one assumes complete debt financing. The equity specification is completely insensitive towards changing financing cost, fosters early wind power deployment, and finally yields lowest carbon prices. The mixed capital one is extremely sensitive towards changing financing cost and postpones wind power deployment towards later periods. The debt specification is also insensitive towards changing discount rates and in general yields lowest investments and highest carbon prices.
Keywords: C61; C68; Q40; Q41; 330; Investment cost; discounting; financing cost; optimization model; power market model